Yellow Canopy Syndrome in sugarcane is associated with shifts in the rhizosphere soil metagenome but not with overall soil microbial function. (October 2018) - Hamonts, Kelly; Trivedi, Pankaj; Grinyer, Jasmine; Holford, Paul; Drigo, Barbara; Anderson, Ian A.; Singh, Brajesh K.
Abstract: The Australian sugarcane industry is facing a new threat of the currently undiagnosed Yellow Canopy Syndrome (YCS). Here, we investigated if YCS is linked to detrimental shifts in soil microbial function and/or altered physico-chemical soil properties. We examined changes in rhizosphere soil microbial assemblages, functional gene profiles and microbial activity associated with YCS development. Shifts in soil bacterial and fungal community assemblages with YCS appeared variety-specific with limited consistent trends emerging. However, significant, consistent shifts in the rhizosphere soil metagenome with YCS were found, suggesting that YCS incidence might be linked to changes in specific soil microbial functions. Functional gene categories involved in prokaryotic immune response and in metabolism of compounds present in root exudates were consistently detected in higher abundance in the rhizosphere of YCS-affected plants, while gene categories involved in DNA, RNA and protein processing were consistently less abundant. Soil nutrient status (C, N), extracellular enzyme activity and substrate-induced respiration either did not significantly differ between affected and healthy fields of three sugarcane varieties, or showed inconsistent trends with variety. Altogether, our results did not show a direct link between soil microbial richness, overall soil microbial activity, soil nutrient status and YCS incidence. However, rhizosphere microbial communities responded consistently to YCS incidence by enrichment of genes encoding functions involved in defence against pathogens and root exudate metabolism which may have potential implications for the future development of diagnostic tools and an effective management practice to minimise impact of YCS on farm productivity. Highlights: Yellow canopy syndrome induced consistent shifts in the rhizosphere soil metagenome. YCS promoted enrichment of genes associated with defence against pathogens and root exudate metabolism. Soil nutrients and enzyme activities demonstrated inconsistent response to YCS.